The summer of Jordi Perez (and the best burger in Los Angeles) - Spalding, Amy (Sky Pony Press, 2020)
Seventeen, fashion-obsessed, and gay, Abby Ives lands an internship at her favorite boutique. She then falls for her fellow intern, Jordi Perez, and finds herself competing against Jordi to win the paid job at the end of the internship. As Abby begins to feel more confident, her new best friend Jax helps her find the best burger in Los Angeles, to prove to Abby's mother, the health nut, that Abby is her own woman. But when her self-esteem reaches its peak, Jordi publishes photographs that cause Abby to feel betrayed, and reconcile her private sense of self-worth and the image others have of her.